Analysis of Influence of Training and Work Motivation on Performance of Employees in General Hospitals Ogan Komering ULU Timur - Wahid Eka Saputra (Komunitas Dosen Indonesia, 2019)
The purpose of the research, from the results of data processing can be seen that the regression Y = 0.148 0.124 X 1 + 0.909 X 2 is very very significant and linear meaning a constant of 0.148 states if there is no training and work motivation then the performance of Employees at Regional General Hospital Hospital) Ogan Ogan Ulu Timur will be fixed at 0.148, the regression coefficient X 1 amounted to 0.124 states that each additional 1 point score motivation to work will improve the performance of clerks at the General Hospital (Hospital) Ogan Ogan Ulu Timur amounted to 0.124 points, the regression coefficient X 2 amounted to 0.909 states that each addition of 1 work motivation point will improve the performance of Employees at the East Ogan Komering Ulu Regional General Hospital (RSUD) by 0.909 points. Suggestions / recommendations, Regional General Hospital (RSUD) Ogan Komering Ulu Timur related to training required technical skills, social abilities, conceptual abilities, so that employees can quickly complete work, work motivation needs to be improved through education, through promotion, and through mutation, about performance is needed to improve employee training and employee motivation in the economy, especially on incentives. Based on the results of this study, there are several implications as follows: to improve employee work discipline in the field of assurance and health facilities in leadership style needs to be improved leadership style indicators of participation type, employee work motivation needs to be improved indicators of work motivation counseling or guidance, regarding employee work discipline socialization of regulations and approaches to persuasion needs to be improved for employees